The Effects of the Five Percent Uniform Tariff on Agriculture - Loreli C. de Dios (Philippine Institute for Development Studies (PIDS), 1997)
Despite commitments to the WTO and the AFTA, many agricultural commodities continue to enjoy protection in the form of tariffs and quotas. Still, the sector has performed dismally relative to other countries. Using tariffs alone, corn producers possess comparative advantage under the 5 percent uniform tariff rate. However, using import prices, they become uncompetitive. Indeed, interventions fail to produce desired results in terms of credit and marketing support. With the various governmental concerns regarding food stability and security, intervention in the agriculture sector has not yet achieved the desired impact.
Keywords: 330; trade sector; agriculture sector; uniform tariff rate; effective protection rate; shadow exchange rate; net present values; producer subsidy equivalent